An Investigation of Collaboration Processes in an Online Course: How do Small Groups Develop over Time? - Jahng, Namsook (International Review of Research in Open and Distributed Learning, 2012)
This study investigated communication patterns and behavior in problem-solving groups in a graduate online course. An inductive qualitative analysis method was employed to analyze 732 messages that were retrieved from small group forums. The current study identified a temporal pattern of group development was in comparison with existing theoretical models: the traditional group development model (Tuckman, 1965; Tuckman & Jensen, 1977) and the punctuated equilibrium model (Gersick, 1988; 1991). All the groups had two working phases and three decision-making points. The temporal pattern of group behavior was close to the phase transition concept of Gersick’s model. Some groups tended to undergo Tuckman’s stages, but their development stages were not necessarily sequential or hierarchical. Thus, it is concluded that Gersick’s model could be more useful for researchers and instructors to better understand and assist online students in problem solving collaborative activities.